2021
DOI: 10.13031/trans.14017
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Conservation Crop Rotation for Water Pollutant Reduction from Agricultural Areas

Abstract: HighlightsAdjusting nitrogen (N) fertilization rates for corn following legumes can reduce N losses.Including perennial legumes in corn rotations can reduce nitrate-N losses and improve water quality.Crop rotations that include three or more years of legumes can be cost-effective.Corn-soybean was the most cost-effective, with a net benefit in nitrate-N loss reduction compared to continuous corn.Abstract. Legumes included in corn-based crop rotation systems provide a variety of benefits to the subsequent crops … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 98 publications
(199 reference statements)
0
8
0
Order By: Relevance
“…The high effectiveness of such zones was also noted in a study by [120], in which nitrate concentrations exceeding 100 mg/L were reduced by 99% with a zone width of 45 m. Finally, an interesting pattern to reduce the nitrate contamination of streams could be the use of crop rotation with leguminous plants, which are known for their major role in nutrient capture in soils [121]. It was proven that crop rotation with leguminous plants generally produces lower nitrogen runoff to groundwater and further streams than monocultures [122,123]. Such solutions require careful overall consideration and attention by managers on a local scale, as agriculture nonpoint sources remain a significant problem in such areas.…”
Section: Recommendations and Limitationsmentioning
confidence: 77%
“…The high effectiveness of such zones was also noted in a study by [120], in which nitrate concentrations exceeding 100 mg/L were reduced by 99% with a zone width of 45 m. Finally, an interesting pattern to reduce the nitrate contamination of streams could be the use of crop rotation with leguminous plants, which are known for their major role in nutrient capture in soils [121]. It was proven that crop rotation with leguminous plants generally produces lower nitrogen runoff to groundwater and further streams than monocultures [122,123]. Such solutions require careful overall consideration and attention by managers on a local scale, as agriculture nonpoint sources remain a significant problem in such areas.…”
Section: Recommendations and Limitationsmentioning
confidence: 77%
“…Careful consideration of crop selection and rotation is also essential in minimizing the risk of HAB contamination (Koropeckyj-Cox et al, 2021). Compared to legumes, crops such as lettuce, corn, and tomatoes exhibit greater susceptibility to HAB toxin accumulation (Saqrane et al, 2009;Melaram et al, 2022).…”
Section: Management Strategiesmentioning
confidence: 99%
“…The impact of constructed wetland on dissolved P in subsurface discharge was highly variable depending on the influent source, and the mean concentration reduction is a negative value (-31%), which means that, on average, the dissolved P concentration is higher in constructed wetland effluent than in the influent. Finally, one study (Koropeckyj-Cox et al, 2021) showed that corn-soybean rotation reduces dissolved P by 39% and corn-soybean-wheat rotation reduces dissolved P by 58%, but further research is needed to better understand the effectiveness of crop rotation in reducing dissolved P.…”
Section: Agricultural Conservation Practicementioning
confidence: 99%
“…The cost-benefit analysis methods for conservation crop rotation and nutrient management effectiveness were based on simple calculations of net revenue, i.e., subtracting the total costs of production from the gross revenues from crop sales for each management scenario (Koropeckyj-Cox et al, 2021;Liu et al, 2021). This is similar to the USDA-NRCS (2020) recommended method of comparing practice benefits to costs and estimating the net effects.…”
Section: Conservation Crop Rotation and Nutrient Managementmentioning
confidence: 99%